KARAKTERISTIK KUALITAS AIR KOLAM BETON PADA BUDIDAYA IKAN NILA (Orechromis niloticus) DI DESA LESENG, SUMBAWA - Astutiwati (Program Studi Ilmu Perikanan, Fakultas Ilmu dan Teknologi Hayati, Universitas Teknologi Sumbawa, 2025)
Water quality is a key factor determining the success of Nile tilapia (Oreochromis niloticus) culture, particularly in concrete pond systems that require intensive environmental management. This study aimed to analyze the characteristics of water quality in concrete ponds used for Nile tilapia culture in Leseng Village, Sumbawa Regency, and to examine their relationship with fish growth and survival rate. The study employed a descriptive quantitative method by collecting water samples from three concrete ponds, with 2–3 sampling points in each pond. The observed water quality parameters included pH, total dissolved solids (TDS), dissolved oxygen (DO), temperature, and nitrite. The data were analyzed descriptively and compared with standard water quality criteria for Nile tilapia culture. The results showed that pH values ranged from 7.27 to 7.86, TDS from 151.5 to 160.0 mg/L, DO from 5.7 to 6.1 mg/L, temperature from 28.7 to 29.2 °C, and nitrite concentration was 0.1 ppm. All measured parameters were within optimal ranges and suitable to support Nile tilapia culture. Stable water quality conditions contributed positively to fish growth and maintained a high survival rate. Therefore, the concrete ponds used for Nile tilapia culture in Leseng Village can be considered suitable as a culture medium and have the potential to support sustainable Nile tilapia aquaculture. Keywords: Water quality, Concrete pond, Aquaculture, Nile tilapia